Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To solve this problem, we need to expand the left-hand side of the given equation [tex]\((a x + 2)(b x + 7)\)[/tex] and compare it to the right-hand side [tex]\(15 x^2 + c x + 14\)[/tex].
Let's expand the left side step-by-step:
[tex]\[ (a x + 2)(b x + 7) \][/tex]
Using the distributive property (FOIL method):
[tex]\[ (a x + 2)(b x + 7) = a b x^2 + 7 a x + 2 b x + 14 \][/tex]
Combining the [tex]\(x\)[/tex] terms:
[tex]\[ = a b x^2 + (7 a + 2 b) x + 14 \][/tex]
Next, we'll match the coefficients from the left side to the right side of the equation [tex]\(15 x^2 + c x + 14\)[/tex]:
1. Coefficient of [tex]\(x^2\)[/tex]:
[tex]\[ a b = 15 \][/tex]
2. Coefficient of [tex]\(x\)[/tex]:
[tex]\[ 7 a + 2 b = c \][/tex]
3. Constant term:
[tex]\[ 14 = 14 \quad (\text{This is automatically satisfied.}) \][/tex]
We are given the additional relation [tex]\(a + b = 8\)[/tex]. Now we need to solve for [tex]\(a\)[/tex] and [tex]\(b\)[/tex] using the equations [tex]\(a b = 15\)[/tex] and [tex]\(a + b = 8\)[/tex].
We have two simultaneous equations:
1. [tex]\(a b = 15\)[/tex]
2. [tex]\(a + b = 8\)[/tex]
We solve these equations to find the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex].
[tex]\[ a + b = 8 \implies b = 8 - a \][/tex]
Substitute [tex]\(b\)[/tex] into the first equation:
[tex]\[ a (8 - a) = 15 \implies 8a - a^2 = 15 \implies a^2 - 8a + 15 = 0 \][/tex]
This is a quadratic equation. Solve it using the quadratic formula [tex]\(a = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = -8\)[/tex], and [tex]\(c = 15\)[/tex]:
[tex]\[ a = \frac{8 \pm \sqrt{64 - 60}}{2} = \frac{8 \pm \sqrt{4}}{2} = \frac{8 \pm 2}{2} \][/tex]
This gives us two values for [tex]\(a\)[/tex]:
[tex]\[ a = \frac{8 + 2}{2} = 5 \quad \text{and} \quad a = \frac{8 - 2}{2} = 3 \][/tex]
Corresponding [tex]\(b\)[/tex] values are:
[tex]\[ \text{If } a = 5, \text{ then } b = 8 - 5 = 3 \][/tex]
[tex]\[ \text{If } a = 3, \text{ then } b = 8 - 3 = 5 \][/tex]
So the pairs [tex]\((a, b)\)[/tex] that satisfy the conditions are [tex]\((5, 3)\)[/tex] and [tex]\((3, 5)\)[/tex].
Next, we use these pairs to find the two possible values of [tex]\(c\)[/tex]:
1. For [tex]\(a = 5\)[/tex] and [tex]\(b = 3\)[/tex]:
[tex]\[ 7a + 2b = 7(5) + 2(3) = 35 + 6 = 41 \][/tex]
2. For [tex]\(a = 3\)[/tex] and [tex]\(b = 5\)[/tex]:
[tex]\[ 7a + 2b = 7(3) + 2(5) = 21 + 10 = 31 \][/tex]
Thus, the two possible values for [tex]\(c\)[/tex] are:
[tex]\[ \boxed{31 \text{ and } 41} \][/tex]
Let's expand the left side step-by-step:
[tex]\[ (a x + 2)(b x + 7) \][/tex]
Using the distributive property (FOIL method):
[tex]\[ (a x + 2)(b x + 7) = a b x^2 + 7 a x + 2 b x + 14 \][/tex]
Combining the [tex]\(x\)[/tex] terms:
[tex]\[ = a b x^2 + (7 a + 2 b) x + 14 \][/tex]
Next, we'll match the coefficients from the left side to the right side of the equation [tex]\(15 x^2 + c x + 14\)[/tex]:
1. Coefficient of [tex]\(x^2\)[/tex]:
[tex]\[ a b = 15 \][/tex]
2. Coefficient of [tex]\(x\)[/tex]:
[tex]\[ 7 a + 2 b = c \][/tex]
3. Constant term:
[tex]\[ 14 = 14 \quad (\text{This is automatically satisfied.}) \][/tex]
We are given the additional relation [tex]\(a + b = 8\)[/tex]. Now we need to solve for [tex]\(a\)[/tex] and [tex]\(b\)[/tex] using the equations [tex]\(a b = 15\)[/tex] and [tex]\(a + b = 8\)[/tex].
We have two simultaneous equations:
1. [tex]\(a b = 15\)[/tex]
2. [tex]\(a + b = 8\)[/tex]
We solve these equations to find the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex].
[tex]\[ a + b = 8 \implies b = 8 - a \][/tex]
Substitute [tex]\(b\)[/tex] into the first equation:
[tex]\[ a (8 - a) = 15 \implies 8a - a^2 = 15 \implies a^2 - 8a + 15 = 0 \][/tex]
This is a quadratic equation. Solve it using the quadratic formula [tex]\(a = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = -8\)[/tex], and [tex]\(c = 15\)[/tex]:
[tex]\[ a = \frac{8 \pm \sqrt{64 - 60}}{2} = \frac{8 \pm \sqrt{4}}{2} = \frac{8 \pm 2}{2} \][/tex]
This gives us two values for [tex]\(a\)[/tex]:
[tex]\[ a = \frac{8 + 2}{2} = 5 \quad \text{and} \quad a = \frac{8 - 2}{2} = 3 \][/tex]
Corresponding [tex]\(b\)[/tex] values are:
[tex]\[ \text{If } a = 5, \text{ then } b = 8 - 5 = 3 \][/tex]
[tex]\[ \text{If } a = 3, \text{ then } b = 8 - 3 = 5 \][/tex]
So the pairs [tex]\((a, b)\)[/tex] that satisfy the conditions are [tex]\((5, 3)\)[/tex] and [tex]\((3, 5)\)[/tex].
Next, we use these pairs to find the two possible values of [tex]\(c\)[/tex]:
1. For [tex]\(a = 5\)[/tex] and [tex]\(b = 3\)[/tex]:
[tex]\[ 7a + 2b = 7(5) + 2(3) = 35 + 6 = 41 \][/tex]
2. For [tex]\(a = 3\)[/tex] and [tex]\(b = 5\)[/tex]:
[tex]\[ 7a + 2b = 7(3) + 2(5) = 21 + 10 = 31 \][/tex]
Thus, the two possible values for [tex]\(c\)[/tex] are:
[tex]\[ \boxed{31 \text{ and } 41} \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.